2005
DOI: 10.1007/11560319_1
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetic Algorithms to Evolve Behavior in Cellular Automata

Abstract: Abstract.It is an unconventional computation approach to evolve solutions instead of calculating them. Although using evolutionary computation in computer science dates back to the 1960s, using an evolutionary approach to program other algorithms is not that well known. In this paper a genetic algorithm is used to evolve behavior in cellular automata. It shows how this approach works for different topologies and neighborhood shapes. Some different one dimensional neighborhood shapes are investigated with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Still, we mention several characteristic works where EAs are used to evolve shift-invariant transformations or related objects. Bäck and Breukelaar used genetic algorithms to evolve behavior in CA where the authors explored different neighborhood shapes [1]. Sipper and Tomassini [16] proposed a cellular programming algorithm to co-evolve the rule map of non-uniform CA for designing random number generators.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, we mention several characteristic works where EAs are used to evolve shift-invariant transformations or related objects. Bäck and Breukelaar used genetic algorithms to evolve behavior in CA where the authors explored different neighborhood shapes [1]. Sipper and Tomassini [16] proposed a cellular programming algorithm to co-evolve the rule map of non-uniform CA for designing random number generators.…”
Section: Related Workmentioning
confidence: 99%
“…In this regard, Evolutionary Algorithms (EAs) represent an interesting method to investigate known RCA classes concerning these additional design criteria, since exhaustively searching for all possible RCA becomes unfeasible for large local rule sizes. To the best of our knowledge, this research method has not been pursued before, although some authors employed EA to evolve CA featuring certain properties other than reversibility [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…For a somewhat outdated but very detailed overview of works using GA to evolve CA, we refer interested readers to [22]. Bäck and Breukelaar used genetic algorithms to evolve behavior in CA and explored different neighborhood shapes [38]. The authors showed that their approach works for different topologies and neighborhood shapes.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, in [21], [30], [41], evolutionary cellular automata have been used for studying and describing strategies of the prisoner's dilemma game. In [3], the authors studied the use of genetic algorithms for finding rules of cellular automata such that they display a desired behavior focusing on the case of solving the majority problem with cellular automata. Also in [24] and [25], the authors exploited genetic algorithms for evolving cellular automata for specific computational tasks such as density classification and synchronization.…”
Section: Introductionmentioning
confidence: 99%